Community Empowerment in Managing Household Waste (Case Study in Gampong Santan, Ingin Jaya District, Aceh Besar) - Fitria; Yani Prihatina Eka Furda (SIASAT, 2022)
This study aims to describeDoes the community have the awareness and understanding to manage household waste in Gampong Santan, Want Jaya District, Aceh Besar District by using qualitative methods. Determination of informants in this study was carried outbypurposive samplingwith 10 informants. The results showed thatCommunity empowerment in managing household waste is starting to run well as it should. The residents of Gampong Santan have high enthusiasm in participating in the programs that have been carried out in dealing with the waste problem. The people of Gampong Santan have started to have awareness and desire to apply the knowledge they have gained from training in their respective homes. The people of Gampong Santan have also understood what and how waste should be handled properly without leaving a bad impact on their environment.